DEKOLONIALISASI DEMOKRASI DARI PESANTREN SUKOREJO - Azizi (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2014)
The issue raised in this paper is about the fenomena of harmony both NU, MD and LDII communities di Awar-Awar Village Asembagus Situbondo Regency. By used ethnography approach founded that harmony constructed in a social manner by NU, MD and LDII communities and elites of Awarawar village in every day life. Social construction con-sists of three moments that is externalization of religious understanding social institution, objectivation through interaction both people by social institution, and internalization is self identification by socialization. In a social manner, because of it pathernalistic character made elites construction influence to people construction. In a social manner, “pendalungan” (Hybrid culture between Java and Madura ethnic) characteristic also give cultural frame to creating harmony. The harmony condition influence all live aspects of people either in a social manner or economy and culture.